Tunable surface modification of silica nanoparticles through `click' chemistry - Chandran, S. Prathap; Hotha, Srinivas; Bhagavatula L. V. Prasad (Current Science, 2008)
Tuning the surface functionality of silica nanoparticles through a `click' chemistry-based protocol is demonstrated. Pyrene, a fluorophore that displays excimer emission specifically at higher density/concentration is chosen for highlighting the fidelity of surface functionalization. The UV-visible absorbance of the pyrene chromophore capping the nanoparticle is used to determine the amount of pyrene units present on the surface of a silica nanoparticle.
Keywords: pyrene; silica nanoparticles; surface functionality; `Click' chemistry

Correlation of architecture with excimer emission in 100% pyrene-labeled self-assembled polymers - Kaushlendra, K.; Deepak, V. D.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2011)
Pyrene was incorporated as pendant unit to side-chain urethane methacrylate polymers having a short ethyleneoxy or a long polyethyleneoxy spacer segment. The short-spacer pyrene urethane methacrylate was also incorporated either as block or random copolymer (1:9) along with polystyrene. The excimer emission was observed to be different for different polymers with the random copolymer exhibiting the lowest efficiency. But, the total quantum yield was highest (phi = 0.58) for random copolymer due to the high emission coefficient of monomer compared to that of excimer. The polymer dynamics were compared by steady state emission and fluorescence decay in THF or THF/water (9:1) solvent mixture and films. The solid state decay profile showed decay without a rise time indicating presence of ground state aggregates. In THF/water (9:1), the decay profile at the excimer emission (500 nm) showed a rise time indicating dynamic excimers. The evolution of excimeric emission centred similar to 430 or similar to 480 nm as a function of temperature was also studied in THF/water (9:1). The I(E)/I(M) ratio for the lambda(343) nm excitation exhibited steady increase with temperature with the block copolymer PS-b-PIHP exhibiting the highest ratio and highest rate of increase; whereas, the random copolymer PS-r-PIHP had the lowest I(E)/I(M) ratios. (C) 2011 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 49: 1678-1690, 2011
Keywords: I(E)/I(M) ratio; Morphology; pyrene; Self-assembly; structure-property relations; time-resolved and variable temperature fluorescence

Fluorescent polystyrene microbeads as invisible security ink and optical vapor sensor for 4-nitrotoluene - Sonawane, Swapnil L.; Asha, S. K. (ACS Applied Materials & Interfaces, 2016)
Color-tunable solid-state emitting polystyrene (PS) microbeads were developed by dispersion polymerization, which showed excellent fluorescent security ink characteristics along with sensitive detection of vapors of nitro aromatics like 4 nitro toluene (4-NT). The fluorophores pyrene and perylenebisimide were incorporated into the PS backbone as acrylate monomer and acrylate cross-linker, respectively. Solid state quantum yields of 94 and 20% were observed for the pyrene and perylenebisimide, respectively, in the PS/Py and PS/PBI polymers. The morphology and solid state fluorescence was measured by SEM, fluorescence microscopy, and absorbance and fluorescence spectroscopy techniques. The ethanol dispersion of the polymer could be used directly as a fluorescent security ``invisible'' ink, which became visible only under ultraviolet light. The color of the ink could be tuned depending on the amounts of the pyrene and perylenebisimide incorporated with blue and orange-green for pyrene alone or perylenebisimide alone beads respectively and various shades in between including pure white for beads incorporating both the fluorophores. More than 80% quenching of pyrene emission was observed upon exposure of the polymer in the form of powder or as spin-coated films to the vapors of 4-NT while the emission of perylenebisimide was unaffected. The limit of detection was estimated at 10(-5) moles (2.7 ppm) of 4-NT vapors. The ease of synthesis of the material along with its invisible ink characteristics and nitro aromatic vapor detection opens up new opportunities for exploring the application of these PS-based materials as optical sensors and fluorescent ink for security purposes.
Keywords: dispersion polymerization; invisible security ink; Perylenebisimide; pyrene; solid state detection

Boron-conjugated pyrenes as fluorescence-based molecular probes and security markers - Wakchaure, Vivek Chandrakant; Das, Tamal; Babu, Sukumaran Santhosh (ChemPlusChem, 2019)
Boron-embedded aromatic hydrocarbons are a class of molecules known for their distinct electronic and/or optoelectronic properties and are thus suitable for many potential applications. Among those, boronic ester and acid containing molecules have been widely used for sensing and molecular recognition applications, respectively. We compared the sensing and molecular recognition properties of two boron-containing pyrene derivatives for fluoride and glucose sensing applications. The presence of four boronate ester groups enabled fluoride ion sensing at the mu M level. The boronic acid derivative is very selective towards glucose compared to other saccharides. Furthermore, we used the mechano-responsive fluorescence changes and self-assembly of these derivatives, respectively, for fluorescence-based inkless and ink (water)-based writing in invisible security labeling applications.
Keywords: boron; carbohydrates; mechanoluminescence; pyrene; sensors

Diamondoid all-carbon porous aromatic framework host for lithium-sulfur batteries - Kumar, Viksit; Javaregowda, Bharathkumar H.; Devasia, George; Narayanan, Aswini; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Small, 2025)
Lithium-sulfur batteries (LSBs) hold incredible potential as next-generation energy storage systems. However, practical applications of LSBs are significantly hindered by several critical challenges. For the first time, scalable all-carbon porous 3D polymers (3DPs) that do not contain heteroatoms or functional groups and do not require post-functionalization are investigated as hosts in lithium-sulfur batteries, demonstrating enhanced cycling stability and overall battery performance. The pyrene-containing 3DP exhibits 75% capacity retention after 600 cycles at 1 C and 52% capacity retention after 1300 cycles at 0.2 C, better than phenyl comprising 3DP. Furthermore, even at higher sulfur loading (4.1 mg cm(-2)) with an electrolyte/sulfur ratio of 5 mu L mg(-1), pyrene 3DP displayed a high capacity of 600 mA h g(-1) and stable performance over 250 cycles with negligible capacity fade. The defined pore structure of 3DPs prevents the migration of polysulfides through physical confinement and the large pi -clouds of 3DPs interact with the negative charge-bearing polysulfides generated in charge-discharge cycles through anion-pi interaction. In this way, The design ensures that the host 3DPs interact with neutral sulfur and anionic polysulfides, resulting in an excellent performance.
Keywords: 3D polymers; Batteries; Li-Sulfur battery; porous materials; pyrene